Membangkitkan Semangat Orang Muda Katolik Dalam Berkatekese - Petriana Dae Lelangwayan; Intansakti Pius X (Jurnal Magistra, 2024)
Catechesis is an important aspect in building the spirit of young Catholics in their faith formation. This article has a catechetical role in forming the foundations of young people's spiritual life and overcoming challenges in the process of faith development. With reference to Church documents that emphasize the importance of catechesis, this article discusses some strategies that can be used to increase the participation of young people in catechesis, including the use of technology as well as involvement in church activities. The research method used in this article is a qualitative method with an observation and literature study approach. The researcher observes young people in catechesis and collects data from articles, journals, and books that are appropriate to the topic discussed. In addition, the article discusses the challenges that young people face in catechesis, such as a lack of understanding of the relevance of catechesis, academic pressures, as well as the influence of secular culture. Considering these challenges, this article may suggest strategies to overcome the boredom that young people experience in blessing and also the importance of listening to the views and experiences of young people. As such, this article aims to awaken the spirit of parents in blessing and strengthen the foundation of their faith.